(Info)Graphically Inclined: A framework of infographic learning. (3rd January 2021) - Smith, Jennifer M.; Robertson, Marla K.
Abstract: Infographics are appearing in children's magazines, picture books, and informational texts. Understanding, and ultimately creating, these complex visual representations of information or data requires higher level thinking skills to analyze and understand how the text and graphics work together to convey meaning. The authors provide a framework for infographic exploration, investigation, creation, and integration into larger writing pieces. Each phase of the framework includes specific considerations to assist teachers in scaffolding their students' infographic learning. Providing students with support through exposure to many types of infographics and modeling infographic interpretation prepares students to critically examine and use infographics as they encounter them both in and out of school.